2021
DOI: 10.14744/tjtes.2021.50245
|View full text |Cite
|
Sign up to set email alerts
|

Our experience on Fournier’s gangrene in a tertiary-stage care center and analysis of its relationship with blood count parameters

Abstract: BACKGROUND: Fournier's gangrene (FG) is rapidly progressing and life-threatening necrotizing fasciitis of genital and perineal regions. The aim of the study was to share our experience with FG and to analyze the relationship of clinical data with whole blood count parameters, inflammation cells, and systemic inflammation markers. METHODS:The digital medical records of the adult patients followed-up and treated with diagnosis of FG between January 2016 to December 2020 were retrospectively analyzed. Data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The use of potent antibiotics has decreased the mortality rate to less than 40% over the past 15 years [4]. Kuzaka et al [2] and Topuz et al [5] reported mortality rates of 0% among patients with FG in 2018 and 2022, respectively. This study examined 40 cases of FG treated at a hospital over the past 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…The use of potent antibiotics has decreased the mortality rate to less than 40% over the past 15 years [4]. Kuzaka et al [2] and Topuz et al [5] reported mortality rates of 0% among patients with FG in 2018 and 2022, respectively. This study examined 40 cases of FG treated at a hospital over the past 10 years.…”
Section: Introductionmentioning
confidence: 99%